Risk factors and state-of-the-art indications for boost irradiation in invasive breast carcinoma - Polo, Alfredo; Polgar, Csaba; Hannoun-Levi, Jean-Michel; Guinot, Jose-Luis; Gutierrez, Cristina; Galalae, Razvan; Van Limbergen, Erik; Strnad, Vratislav (Brachytherapy, 2017)
PURPOSE: The aim of the study was to give recommendations on patient selection criteria for the administration of boost doses after whole-breast irradiation (WBI) in invasive breast cancer based on available clinical evidence complemented by expert opinion. METHODS AND MATERIALS: A systematic search of the PubMed database was conducted to identify factors associated with increased risk for local failure that can define risk groups, and to provide evidence for an adequate guidance to the use of the boost as a function of the risk of local recurrence in breast-conserving therapy. The authors reviewed the published clinical evidence for the use of boost after WBI, complemented by other relevant studies and, through a series of formal meetings communications, formulated the recommendations presented in this article. RESULTS: The GEC-ESTRO Breast Cancer Working Group recommends three categories guiding patient selection for the use of a boost after WBI: (1) a low-risk group for whom boost adds little benefit, including patients aging at least 50 years with unicentric, unifocal, and clear surgical margins of at least 2 mm and no axillary lymph nodes invasion. In this group, a boost of 10-16 Gy EQD2 after WBI (25fr × 2 Gy or 15 fr × 2.67 Gy) is optional and not mandatory, (2) a high-risk group, for whom boost is considered mandatory and where dose escalation above 16 Gy EQD2 should be considered; including patients aging ≤40 years with close margins, extensive intraductal component or triple-negative phenotype, or patients with positive resection margins regardless of patient age, and (3) an intermediate-risk group, for whom the boost (10-16 Gy EQD2) is considered mandatory, includes patients below 40 years without major risk criteria, patients >40 years and <50 years regardless of any risk factors, or patients >50 years with any risk factor (close margins, tumor size >3 cm, extensive intraductal component, lymphovascular invasion, lymph node invasion, multicentric or multifocal tumors, triple-negative phenotype, or after neoadjuvant chemotherapy in case of residual tumor). CONCLUSIONS: These recommendations may provide a clinical guidance regarding the use of boost after WBI in invasive breast cancer and holds for standard and hypofractionated WBI. Furthermore they should promote further clinical research focusing on controversial issues in the treatment of early-stage breast carcinoma.
EVALuna2:36543